Assessment Method Of Study Program: Results From Regression Analysis - Mohd Rashid, Ab Hamid; Mohd Rusllim, Mohamed; Zainol, Mustafa (2015)
Assessment is an important part in any universities programs. Various approach of assessment has been used in determining the students’ grade for the subjects. Therefore, this article discussed the empirical study for finding the best solution for determining the student grades. Several predictors for determining the students’ grades i.e. total marks were identified such as coursework marks, mid-semester marks and final exam marks. Therefore, raw data from the database for a particular semester at one university in east coast of Malaysia are used for this purpose. The Correlational analysis was used to determine the strength of the association between the three predictors and the criterion variable. Also, multiple regression analysis was used to find the best regression model for the purpose of the study. Implications of the study were also discussed.